Transcriptional induction of the ubiquitin gene during herpes simplex virus infection is dependent upon the viral immediate-early protein ICP4. - Latchman, D S (1987)
Lytic infection with herpes simplex virus results in transcriptional induction of a cellular gene encoding ubiquitin, causing increased accumulation of ubiquitin RNA and protein in the infected cell. This induction, which is dependent upon viral protein synthesis, does not occur in the HSV-1 mutant tsK which is defective in the gene encoding the viral protein ICP4. Transfected cells expressing the viral ICP4 protein exhibit higher levels of ubiquitin gene transcription than untransfected controls indicating that transcriptional induction can be mediated by the ICP4 protein alone.